eling the Humanitarian Intervention Dilemmas and Failures of the United Nations in “Quo Vadis, Aida?” Film - Purwanto, Cynthia Syukur (Jurnal Sentris, 2024)
This journal explores the United Nations' (PBB) intervention in the conflict between Bosnia-Herzegovina and Serbia, with a particular focus on the tragic events depicted in the film "Quo Vadis, Aida?" The study delves into the challenges faced by the UN, an actor well-known for their conflict resolution since World War, but it is relatively new in finding resolutions in terms of conflict between ethnicity, and its attempts to balance humanitarian and military interests. Despite initial efforts created by the UN, the actions were deemed as failures as the pinnacle of the conflict is Srebenica Genocide. Through this research, the author aims to find the factors behind the failed efforts in peacekeeping in Bosnia-Herzegovina. Keywords: Srebrenica Genocide; The United Nations; Humanitarian Intervention.